Personal mental health navigator: Harnessing the power of data, personal models, and health cybernetics to promote psychological well-being - Rahmani, Amir M.; Lai, Jocelyn; Jafarlou, Salar; Azimi, Iman; Yunusova, Asal; Rivera, Alex. P.; Labbaf, Sina; Anzanpour, Arman; Dutt, Nikil; Jain, Ramesh; Borelli, Jessica L. (Frontiers in Digital Health, 2022)
Existing digital mental healthcare solutions commonly take on a reactive approach, requiring individuals to self-monitor and document symptoms. Recognizing the need for more comprehensive, objective monitoring and that each individual may benefit from personally tailored treatment, we present the notion of Personalized Mental Health Navigation (MHN): a cybernetic goal-based system that deploys a continuous cyclic loop of monitoring, estimation, and guidance to steer the individual towards mental flourishing. We first outline the core components of MHN that are premised on the development of an individual’s personal mental health state and then provide an overview of the monitoring features. We demonstrate the initial feasibility of the monitoring features of MHN by providing data and results from a pilot study following young adults across a 12-month period.